2024
DOI: 10.3389/fcimb.2024.1360438
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of natural Wolbachia in Aedes aegypti in Metropolitan Manila, Philippines using locally designed primers

Jerica Isabel L. Reyes,
Takahiro Suzuki,
Yasutsugu Suzuki
et al.

Abstract: BackgroundThe Philippines bears health and economic burden caused by high dengue cases annually. Presently, the Philippines still lack an effective and sustainable vector management. The use of Wolbachia, a maternally transmitted bacterium, that mitigate arbovirus transmission has been recommended. Cytoplasmic incompatibility and viral blocking, two characteristics that make Wolbachia suitable for vector control, depend on infection prevalence and density. There are no current Wolbachia release programs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Notably, Wolbachia natural infection has been scarcely recorded in Anopheles and Ae. aegypti mosquitoes, with a few studies conducted in Malaysia 26 , 33 , Thailand 34 , 35 , Myanmar 36 , Philippines 37 , 38 , Panama 39 , New Mexico and Florida, USA 40 , and various regions in Africa 41 45 . A study by Wong and colleagues in Malaysia 26 reported Wolbachia infection in both Anopheles mosquitoes ( An.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Wolbachia natural infection has been scarcely recorded in Anopheles and Ae. aegypti mosquitoes, with a few studies conducted in Malaysia 26 , 33 , Thailand 34 , 35 , Myanmar 36 , Philippines 37 , 38 , Panama 39 , New Mexico and Florida, USA 40 , and various regions in Africa 41 45 . A study by Wong and colleagues in Malaysia 26 reported Wolbachia infection in both Anopheles mosquitoes ( An.…”
Section: Discussionmentioning
confidence: 99%
“…This is an unusually high diversity of Wolbachia given that interactions among Wolbachia strains based on host effects associated with the Wolbachia typically drive some Wolbachia out of populations as well documented in Drosophila (Kriesner et al., 2013 ). The presence of multiple Wolbachia strains was supported by additional work using different locally developed primers for common markers (Reyes et al., 2024 ), with a novel low‐density strain being detected. However, it is worth noting that all three molecular papers now developed from Manila (including Carvajal et al., 2019 ) have used the same original Ae .…”
Section: Challenges In New Studiesmentioning
confidence: 95%